فاعلية نموذج دانيال المعرفي في تنمية مهارات توليد المعلومات والاتجاه نحو العلوم لدى طالبات المرحلة المتوسطة بمدينة مكة المكرمة - الزهراني، غالية بنت أحمد خلف; بابطين، هدى بنت محمد بن حسين (رابطة التربويين العرب, 2024)
هدفت الدراسة إلى الكشف عن فاعلية نموذج دانيال المعرفي في تنمية مهارات توليد المعلومات والاتجاه نحو العلوم لدى طالبات المرحلة المتوسطة بمدينة مكة المكرمة؛ وتم استخدام المنهج التجريبي ذي التصميم شبه التجريبي لمجموعتين بلغت (٥٨) طالبة تجريبية (٢٩) طالبة وضابطة (29) طالبة ذاتا القياسين القبلي والبعدي، وطبقت الدراسة خلال الفصل الدراسي الثاني من العام الدراسي (1441ه/ 1442ه)، حيث درسن وحدة النباتات وموارد البيئة باستخدام نموذج دانيال المعرفي، وتم تطبيق أداتي الدراسة: اختبار مهارات توليد المعلومات، ومقياس الاتجاه نحو العلوم، اللتين كانتا من إعداد الباحثة، ولاختبار صحة فروض الدراسة عولجت بياناتهما إحصائيا بعد التطبيق البعدي للأداتين باستخدام المتوسطات الحسابية، والانحرافات المعيارية، واختبار (T) للمجموعات المستقلة، ومعادلة (2) لحساب حجم الأثر، ومعامل الارتباط بيرسون لإيجاد العلاقة بين المتغيرين التابعين، معادلة كرونباخ ألفا لحساب ثبات كل من: اختبار مهارات توليد المعلومات، ومقياس الاتجاه نحو العلوم. كشفت نتائج الدراسة: وجود فروق دالة إحصائيا عند مستوى الدلالة (α ≤ 0.05) بين متوسطات درجات طالبات المجموعتين التجريبية والضابطة في القياس البعدي لاختبار مهارات توليد المعلومات؛ لصالح المجموعة التجريبية، ووجود فروق دالة إحصائيا عند مستوى الدلالة (α ≤ 0.05) بين متوسطات درجات طالبات المجموعتين التجريبية والضابطة في القياس البعدي لمقياس الاتجاه نحو العلوم لصالح المجموعة التجريبية، كما وجدت علاقة إيجابية قوية ذات دلالة إحصائية عند مستوى الدلالة (α ≤ 0.05) بين متوسطات درجات طالبات المجموعة التجريبية في القياس البعدي لاختبار مهارات توليد المعلومات، ومقياس الاتجاه نحو العلوم تعزى للتدريس باستخدام نموذج دانيال المعرفي، وفي ضوء هذه النتائج أوصت الدراسة بعدة توصيات أهمها: توظيف نموذج دانيال المعرفي في تدريس مادة العلوم. The aim of the present study was to identify the effectiveness of the Daniel's cognitive model in developing information generation skills and the trend towards science, a quasi-experimental design of two groups The study sample was (58) students: (29) female students as experimental group The study sample studied the unit of Plants and environmental resources using the Daniel Cognitive Model and (29) female students in the control group, studied the same unit in the usual method It was applied during the second semester of the academic year 1441/ 1442 AH. The tools, the Testing information generation skills and a measure of attitude towards science, were prepared and applied by the researcher after confirming their validity and reliability. To test the study hypotheses, the data were statistically treated using arithmetic means, standard deviations, T-test for independent groups, equation (2) to calculate the effect size, and Pearson's correlation coefficient to find the relationship between the two variables. The results revealed that there were statistically significant differences at the level of (α ≤ 0.05) between the mean scores of the experimental and control groups, in the post conceptual comprehension test as a whole, in favor of the experimental group. There were statistically significant differences at the significance level (α ≤ 0.05) between the mean scores of the two groups of students, in the measure the trend towards science as a whole, in favor of the experimental group. A statistically significant correlation was also found at the significance level (α ≤ 0.05) between the mean scores of the two groups of students in the tests of Information generation skills and attitude towards science attributed to the use of Daniel's cognitive model in teaching science to the experimental group. In light of these results; the study recommended several recommendations.
Keywords: الاستراتيجيات التعليمية -- نموذج دانيال المعرفي -- طلبة المدارس -- المناهج الدراسية -- السعودية